Effect of brief cetylpyridinium chloride treatments during early and mature cariogenic biofilm formation. (13th February 2015) - Pandit, S; Cai, J‐N; Jung, J‐E; Lee, Y‐S; Jeon, J‐G
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to investigate the antibiofilm activity of brief cetylpyridinium chloride (CPC) treatments during early and mature Streptococcus mutans biofilm formation. Methods Streptococcus mutans biofilms were formed on saliva‐coated hydroxyapatite disks. The biofilms were treated with CPC twice daily (1 min/treatment) from 0 to 50 h or from 48 to 98 h. Acidogenicity, dry weight, viability, and water‐insoluble extracellular polysaccharides of the biofilms were analyzed. Confocal laser scanning microscopy (CLSM) images were obtained to confirm the antibiofilm activity during mature biofilm formation and to evaluate the relationship between treatment time and the antibiofilm activity. Results CPC showed complete antibiofilm activity during early biofilm formation at 0.025% to 0.1%. During mature biofilm formation, CPC inhibited dry weight, viability, and acidogenicity at 0.075% and 0.1%. CLSM images showed an increase in dead cells at 0.075% and 0.1% CPC. The antibiofilm activity during mature biofilm formation increased as the concentration of CPC increased. Images from the CLSM study also showed that antibiofilm activity increased as treatment time increased. Conclusion Our findings suggest that brief CPC treatments have strong anti‐S. mutans biofilm activity. The antibiofilm activity was dependent on the stage of biofilm formation, CPC concentration, and treatment time.